Exchange rate volatility and disaggregated manufacturing exports: Evidence from an emerging country - Duc Hong Vo; Anh The Vo; Zhaoyong Zhang (Journal of Risk and Financial Management, 2019)
The link between export performance and exchange rate policy has been attracting attention from policymakers, academics, and practitioners for some time, particularly for emerging countries. It has been recently claimed that implementing a policy that devalues the currency in Vietnam is an important factor for enhancing its export performance. However, it is also argued that such a policy could result in the harmful consequence of exchange rate volatility. This study analyzes the link between exchange rate devaluation, volatility, and export performance. The analysis focuses on the manufacturing sector and 10 of its subsectors that were engaged in the export of goods between Vietnam and 26 key export partners during the 2000-2015 period. Potential factors that could affect this relationship, such as the global financial crisis, Vietnam's participation in the World Trade Organization, or even the export partners' geographic structures, are also accounted for in the model. The findings confirm that a strategy that depreciates Vietnam's currency appears to enhance manufacturing exports in the short run, whereas the resulting exchange rate volatility has clear negative effects in the long run. The impact of exchange rate volatility on manufacturing subsectors depends on two factors, namely, (i) the type of export and (ii) the export destination. Policy implications emerging from these conclusions are presented.
Keywords: C33; F14; F31; 330; exchange rate volatility; export performance; disaggregated data; manufacturing sector; emerging country